A novel mutation in early‐onset sarcoidosis/Blau syndrome: an association with Propionibacterium acnes - Fumiko Okazaki; Hiroyuki Wakiguchi; Yuno Korenaga; Tamaki Nakamura; Hiroki Yasudo; Shohei Uchi; Ryoji Yanai; Nobuyuki Asano; Yoshinobu Hoshii; Tsuyoshi Tanabe; Kazushi Izawa; Yoshitaka Honda; et al. (BMC, 2021)
Abstract Background Early-onset sarcoidosis (EOS) and Blau syndrome (BS) are systemic inflammatory granulomatous diseases without visible pulmonary involvement, and are distinguishable from their sporadic and familial forms. The diseases are characterized by a triad of skin rashes, symmetrical polyarthritis, and recurrent uveitis. The most common morbidity is ocular involvement, which is usually refractory to conventional treatment. A gain-of-function mutation in the nucleotide-binding oligomerization domain-containing protein 2 (NOD2) gene has been demonstrated in this disease; however, little is known about the relationship between the activation of NOD2 and the pathophysiology of EOS/BS. Here we describe EOS/BS with a novel mutation in the NOD2 gene, as well as detection of Propionibacterium acnes (P. acnes) in the granulomatous inflammation. Case presentation An 8-year-old Japanese girl presented with refractory bilateral granulomatous panuveitis. Although no joint involvement was evident, she exhibited skin lesions on her legs; a skin biopsy revealed granulomatous dermatitis, and P. acnes was detected within the sarcoid granulomas by immunohistochemistry with P. acnes-specific monoclonal (PAB) antibody. Genetic analyses revealed that the patient had a NOD2 heterozygous D512V mutation that was novel and not present in either of her parents. The mutant NOD2 showed a similar activation pattern to EOS/BS, thus confirming her diagnosis. After starting oral prednisolone treatment, she experienced an anterior vitreous opacity relapse despite gradual prednisolone tapering; oral methotrexate was subsequently administered, and the patient responded positively. Conclusions We presented a case of EOS/BS with a novel D512V mutation in the NOD2 gene. In refractory granulomatous panuveitis cases without any joint involvement, EOS/BS should be considered as a differential diagnosis; genetic analyses would lead to a definite diagnosis. Moreover, this is the first report of P. acnes demonstrated in granulomas of EOS/BS. Since intracellular P. acnes activates nuclear factor-kappa B in a NOD2-dependent manner, we hypothesized that the mechanism of granuloma formation in EOS/BS may be the result of NOD2 activity in the presence of the ligand muramyl dipeptide, which is a component of P. acnes. These results indicate that recognition of P. acnes through mutant NOD2 is the etiology in this patient with EOS/BS.